Changes in physiological and stroking parameters during interval swims at the slope of the d-t relationship - Paulino Ribeiro, Luiz Fernando; Spiguel Lima, Manoel Carlos; Gobatto, Claudio Alexandre [UNESP] (Sports Medicine Australia, 2010)
The slope of the distance-time relationship from maximal 200 and 400 in bouts (S(200-400)) has been increasingly employed for setting training intensities in swimming. However, physiological and mechanical responses at this speed are poorly understood. Thus, this study investigated blood lactate, heart rate (HR), stroke rate (SR), stroke length (SL) and RPE responses to an interval swimming set at S(200-400) in trained swimmers. In a 50-m pool, twelve athletes (16.5 +/- 1.2 yr, 176 +/- 7 cm, 68.4 +/- 5.4 kg, and 7.8 +/- 2.5% body fat) performed maximal 200 and 400 m crawl trials for S(200-400) determination (1.28 +/- 0.05 m/s). Thereafter, swimmers were instructed to perform 5 x 400 in at this speed with 1.5 min rest between repetitions. Three athletes Could not complete the set (exhaustion at 21.0 +/- 3.1 min). For the remaining swimmers (total set duration = 32.0 +/- 1.3 min) significant increases) (p < 0.05) in blood lactate (5.7 +/- 0.8-7.9 +/- 2.4 mmol/l), SR (29.6 +/- 3.2-32.1 +/- 4.1 cycles/min), HR (169 +/- 11-181 +/- 8 bpm) and RPE (13.3 +/- 1.6-16.3 +/- 2.6) were observed through the IS. Conversely, SL decreased significantly (p < 0.05) from the first to the fifth repetition (2.48 +/- 0.22-2.31 +/- 0.24 m/cycle). These results suggest that interval swimming at S(200-400) represents an intense physiological, mechanical and perceptual stimulus that can be sustained for a prolonged period by most athletes. (C) 2008 Sports Medicine Australia. Published by Elsevier Ltd. All rights reserved.
Keywords: Swimming; Critical speed; Interval training; Blood lactate; Stroking parameters; Perceived exertion